Land Body Ecologies: A case study for global transdisciplinary collaboration at the intersections of environment and mental health - Samrawit Gougsa; Victoria Pratt; Babitha George; Cecilia Vilela; Daniel Kobei; Sylvia Kokunda; Ilan Kelman; Ben Eaton; Lilian Maina; Samson Luari; Outi Autti; Kaisa Kerätär; et al. (Elsevier, 2023)
Land Body Ecologies (LBE) is a global, transdisciplinary research group seeking to understand the mental health dimensions of minority, Indigenous and other land-dependent communities' relationship to ecologies in a changing environment. We posit that our project is a successful case of global transdisciplinary collaboration that can serve as an example for others. In this paper we present: (1) an overview of our project structure across various disciplines and geographies; (2) a description of how we manage day-to-day operations and decision-making; (3) details of how we operationalise collaboration through examples from three key areas - creative methodologies, language considerations and authorship; (4) a discussion on strengths and limitations of the project.